Inclusion and disability: How to build accessible breastfeeding - Introcaso Irazábal, Jimena (UNIVERSITAS. Revista de Filosofía, Derecho y Política, 2025)
There are numerous studies on breastfeeding and disabilities, but few address their intersection. This paper seeks to analyze the cultural, social, economic, occupational, health and communication factors that affect breastfeeding, considering its accessibility deficit, especially for people with disabilities. Although the postpartum period is a global interdisciplinary issue, its approaches do not fully visualize the factors that affect breastfeeding, which intensifies the barriers related to ableism. This study uses intersectionality to identify systemic inequalities that impact the breastfeeding of people with disabilities. Finally, accessible public policies that favour social inclusion and improve governance are suggested
Keywords: Breastfeeding; rights; disability; accessibility; governance; intersectionality